Cross-sectional analysis and prospective observational study of sleep quality, lung function, ventilatory muscle strength, ventilatory patterns, autonomic nervous activity, disease severity, clinical status and quality of life in Myasthenia Gravis: a rese - Oliveira, Ezequiel Fernandes; Nacif, Sergio Roberto; Fonsêca, Nina Teixeira; Santos, Israel Reis; Urbano, Jessica Julioti; Dias, Ismael Sousa; Almeida, Rafael Guia; Apostolico, Nadua; Ferraz, Leonardo Macário; Araújo, Ana Karina Fachini; et al. (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The presence of sleep disorders in Myasthenia gravis (MG) patients, can negatively affect the ventilation and the mechanics of breathing in patients with neuromuscular diseases. Some studies have shown a poor quality of sleep, excessive daytime sleepiness and the presence of sleep disordered breathing, while others did not observe a positive correlation. The aim of the study is to investigate sleep quality, lung function, ventilatory patterns, autonomic nervous activity, disease severity, clinical status and quality of life in clinically stable MG patients. Method: We propose a cross sectional analysis and prospective observational study of sleep quality, lung function, ventilatory patterns, autonomic nervous activity, disease severity, clinical status and quality of life in MG patients which will be conducted at the Sleep Laboratory of Nove de Julho University and the Neuromuscular Research Department of the Federal University of São Paulo. The design, conduct, and reporting of this study will follow the rules of The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Statement. The protocol will includes body weight; height; body mass index; circumferences of the neck, waist, and hip; heart and respiratory rates; Mallampati index; maximum ventilatory pressures; spirometry; and standard overnight polysomnography, as well as the administration of specific questionnaires addressing the risk of obstructive sleep apnoea, excessive daytime sleepiness and HRQoL. Moreover, specific questionnaires addressing sleep apnoea; excessive daytime sleepiness; symptoms of stress, depression, anxiety, disease severity, clinical status and quality of life will be administered. The 8 outcome variables which will be measured include subjective sleepiness Epworth Sleepiness Scale (ESS), risk of OSA through The Berlin Questionnaire, stress and its manifestations by The Inventory of Symptoms of Stress for Adults (LIPP), anxiety and depression by The Hospital Anxiety and Depression Scale (HAD), general quality of life questionnaire using The Short Form 36 (SF36) and specific outcome measure MGQOL 15, MG Composite Scale and The Quantitative Myasthenia Gravis Score. Discussion: This protocol expects to identify the presence and severity of sleep disorders, changes of autonomic nervous activity, HRQoL and consequently contribute to an earlier diagnosis, thus reducing the impact on quality of life of MG patients.